PERLINDUNGAN KONSUMEN TERHADAP MENINGKATNYA PENIPUAN PRODUK YANG DIPERJUALBELIKAN SECARA ONLINE - Fitri Fitri (JOURNAL IURIS SCIENTIA, 2024)
Use of electronic media to function as computerized information when making agreements, organizations that carry out their activities using electronic me- dia, for example the web, will see an impact on their exhibitions. However, considering that the agreement is made online does not mean there are no problems. This problem arises as a result of the increasingly widespread vio- lations that utilize the internet, in particular the widespread misrepresentation online, especially in online conversations. The enactment of Law Number 2 shows the efforts made by public authorities to protect consumers. 8 of 1999, which regulates customer guarantees. where consumer responsibilities and rights have been regulated. In addition, vendors have privileges and commit- ments. Therefore, the author's proposed research subject is "Legal Protection for Consumers Who Are Harmed in Transactions of Buying and Selling Goods in Online Stores". This problem concerns Shopee's policy in protecting con- sumers who are harmed in buying and selling transactions and how to do it. provides legal protection for consumers who suffer losses in buying and sell- ing goods through Shopee e-commerce as outlined in Law Number Concern- ing Consumer Protection Law Number 8 of 1999. This examination uses a juridical strategy which regulates using emotional examination which is cen- tered on the findings. These exploration findings have the opportunity to come to the conclusion that Consumer Insurance Regulation Number 8 of 1999 has made further efforts to protect online exchange trading. To protect online ex- changes, Shopee takes various approaches, including Article 26 which tends to commit, which touches on the regulation of Unofficial Law (PP) number 80 of 2019 concerning Exchanges Through Electronic Frameworks (UU PMSE)